[The London and North-Western Railway Company's Crisis, December 1896]
Recueil d'articles divers parus les 8 et 12 décembre 1896 dans la presse anglaise : "The Yorkshire Post", "The Daily Chronicle", "The Heichley News", "The Midland Counties Express".